Are Public Libraries Improving Quality of Education? : When the Provision of Public Goods is Not Enough - Rodriguez Lesmes, Paul; Trujillo, Jose Daniel; Valderrama, Daniel (Washington, DC, 2015)
This paper analyzes the relation between public, education-related infrastructure and the quality of education in schools. The analysis uses a case study of the establishment of two large, high-quality public libraries in low-income areas in Bogotá, Colombia. It assesses the impact of these libraries on the quality of education by comparing national test scores (SABER 11) for schools close to and far from the libraries before (2000–02) and after (2003–08) the libraries were opened. The paper introduces a Blinder-Oaxaca decomposition on diﬀerence-in-diﬀerences estimates to assess whether variation of traditional determinants of mathematics, verbal, and science test scores explains the estimates. The analysis ﬁnds differences that are not statistically diﬀerent from zero that could be attributed to the establishment of the libraries. These results are robust to alternative speciﬁcations, a synthetic control approach, and an alternative measure of distance.